Solar tracker with wireless charging - Patrus Maximus, Anak Tinggal (Universiti Malaysia Sarawak (UNIMAS), 2017)
Sunlight is a renewable resources because everyday sun will rises and thus, produces sun light. Furthermore, sunlight can be harvested and it is eco-friendly and does not pollute the environment. Plus, by reducing the usage of cables is good for environmental and human’s health. It is called as wireless in short. Do we know, by combining harvesting sunlight and wireless able to reduce large amount of money. Why? It is because materials needed to produce the cables can be cut and human able to avoid themselves from electric shock and by harvesting the sunlight, the electricity bill can be reduced. This project is to design, develop, investigate and analyze the efficiency of wireless charging solar tracker. This solar tracker able to rotate till 3600 by using two servo motors and LDR as a sensor in order to harvest sunlight till maximum and combine with wireless charging by using magnetic resonance coupling method instead of using cable as medium to charge a battery.